2015
DOI: 10.1039/c5ra18089a
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation of biogas producing microcosm for enhancing oil recovery in low-permeability oil reservoir

Abstract: Indigenous microbial enhanced oil recovery (IMEOR) has been successfully applied in conventional oil reservoirs, however the mechanism in low-permeability oil reservoirs is still misunderstood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…To date, a large amount of microbial populations have been isolated or detected in oil reservoirs worldwide (Lenchi et al, 2013; Al-Sayegh et al, 2015; Gao et al, 2016; Okoro et al, 2016; Su et al, 2018). These microorganisms are versatile: some species can degrade crude oil, some can produce biosurfactants (Liu et al, 2015; Cui et al, 2017; Qi et al, 2018), biopolymers (Bi et al, 2016; Xia et al, 2018; Zhao et al, 2018), or biogases (Dong et al, 2015; Zhu et al, 2015), and have been used to mobilize and recover residual oil from oil-bearing rocks (Youssef et al, 2009; Wang et al, 2014; Yi et al, 2018). In addition, nitrate can be used to reduce formation of hydrogen sulfide produced by sulfate-reducing bacteria (SRB) based on the competitive inhibition of nitrate-reducing bacteria on SRB (Gieg et al, 2011; Gassara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a large amount of microbial populations have been isolated or detected in oil reservoirs worldwide (Lenchi et al, 2013; Al-Sayegh et al, 2015; Gao et al, 2016; Okoro et al, 2016; Su et al, 2018). These microorganisms are versatile: some species can degrade crude oil, some can produce biosurfactants (Liu et al, 2015; Cui et al, 2017; Qi et al, 2018), biopolymers (Bi et al, 2016; Xia et al, 2018; Zhao et al, 2018), or biogases (Dong et al, 2015; Zhu et al, 2015), and have been used to mobilize and recover residual oil from oil-bearing rocks (Youssef et al, 2009; Wang et al, 2014; Yi et al, 2018). In addition, nitrate can be used to reduce formation of hydrogen sulfide produced by sulfate-reducing bacteria (SRB) based on the competitive inhibition of nitrate-reducing bacteria on SRB (Gieg et al, 2011; Gassara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was used to evaluate the application potential of the exogenous surfactant-producing B. subtilis in facilitating the IMEOR process. Previous investigations have shown that the stimulation of indigenous microorganisms enhances oil recovery by 3.7–9.14 % ( Bao et al, 2009 ; Dong et al, 2015 ), and by 4.89–24 % in core-flooding tests with surfactant-producing bacteria and their metabolites ( She et al, 2011 ; Castorena-Cortes et al, 2012 ; Xia et al, 2012 ; Gudina et al, 2013 ; Al-Wahaibi et al, 2014 ; Arora et al, 2014 ; Song et al, 2015 ). In this study, the brines with nutrients and fermentation broth of B. subtilis M15-10-1 increased the oil displacement efficiency by 16.71%, which is higher than the 7.59% with nutrient injection only.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing global energy demand and depletion of oil reserves, oil recovery by microbial flooding is currently under intensive development, and has been shown to be economically feasible by laboratory and field trials ( Belyaev et al, 1998 ; Gao and Zekri, 2011 ; Xiao et al, 2013 ; Li et al, 2014 ; Shibulal et al, 2014 ; Dong et al, 2015 ; You et al, 2015 ). This technique is generally classified into exogenous and indigenous microbial enhanced oil recovery (MEOR).…”
Section: Introductionmentioning
confidence: 99%
“…The hypervariable V2–V3 region of the bacterial 16S rRNA gene was amplified with the universal primer set 104F (50-GGC­G­V­A­C­G­G­G­T­G­A­G­T­AA-30) and 530R (50-CCG­C­N­G­C­N­G­C­T­G­G­CAC-30) in a 50 μL PCR mixture containing 25 μL of Taq PCR Mastermix (TIANGEN, Beijing, China), 6 μL of DNA template, 1 μL of primer 104F, 1 μL of primer 530R, and 17 μL of ddH 2 O. The PCR program was similar to that reported by Dong et al . and Xiao et al, with some modifications.…”
Section: Methodsmentioning
confidence: 99%